(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The crisis we are going through has revealed serious systemic inconsistencies and risks. Insistently from different perspectives, a change in the economic model isrequested, in its values and functioning principles. An urgent need to introduce,among others, new dimensions: ethics, social responsibility, sustainability and a wellunderstood long term approach, is demanded. Social Economy and Cooperativism have been proposing for a long time a different business model which stimulates asustainable, more balanced and fair development, based on social and environmental values.